Slavery, Incentives, and Manumission: A Theoretical Model - Findlay, Ronald (Journal of Political Economy, 1975)
This paper presents a theoretical model of slavery and manumission in which the effective labor provided by slaves is a function of both the level of supervision costs incurred by the owner and the incentive payments received by the slaves. The optimal combination of supervision costs and incentive payments is determined together with the input of physical capital. The length of time it would take for a slave to purchase his freedom out of savings from his incentive payments is derived and is shown to vary inversely with the rate of interest.